Nursing in the COVID‐19 pandemic and beyond: protecting, saving, supporting and honouring nurses. (23rd June 2020) - Catton, Howard
Abstract: As the world tackles the largest public health event in more than a century, the COVID‐19 pandemic, the true value of nursing is being seen by politicians and the public. But while nurses are being praised for the vital work they do, many are being put into high‐risk situations, and some have died, because of a shortage of appropriate, high‐quality personal protective equipment. The International Council of Nurses has called for governments to make the provision of such equipment their number one priority to prevent further loss of life among the nurses caring for the world's most vulnerable patients.